Vírus mutante na paisagem de Bauru - Tamai, Sidney [UNESP] (My University, 2013)
This paper presents the work of the MutantVirus. A group which belongs to a subject extension called Public Art Projects in Bauru City from FaacUnesp. It exposes its designs, structures, approaches, procedures, results and reflections, as well as it discusses the point of a Public Art group being associated to the Public University.

Esse artigo busca apresentar o trabalho do grupo VirusMutante da Extensão “Projetos de Arte Pública na cidade de Bauru” da FaacUnesp. Expõe seus vários projetos, estruturas de ação, suas abordagens, processos, procedimentos, resultados e reflexão, além de problematizar a questão de um grupo de Arte Pública articulado a Universidade.
VírusMutantis in Bauru landscape
Keywords: Public art installations; Architecture; Field expanded Arts Architecture; Space-time intervention; Arte Pública; Instalações; Arquitetura; Campo expandido arte-arquitetura; Intervenção espaço-temporal